Description of Patterns For Prevention and Treatment Of Covid-19 in Communities in the Work Area Of Puskesmas Sukaramai Medan in 2021 - Ananda Annisa Batubara; Zaim Anshari (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Background : In early 2020, the world was shocked by the outbreak of a new pneumonia that started in Wuhan which then spread rapidly to more than 190 countries. This outbreak was named Coronavirus Disease 2019 (Covid-19) which was caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). In Indonesia, the first Covid-19 case was reported on March 2, 2020. Since then, cases have continued to increase and spread rapidly throughout Indonesia.Objective : Description of prevention and treatmentpatterns Covid 19 in the work area of the community health center Sukaramai Medan.Methods : This research is a qualitative study with a cross sectional designResults : Based on the results of this study, it can be seen that 40 respondents (75,5%) prevent the spread of COVID-19 and 13 respondents (24,5%) don’t prevent the spread of COVID-19. 21 respondents (39,6%) taking drugs outside of a doctor's prescription during the isolation period and 32 respondents (60,4%) do not takung drugs outside of a doctors’s prescription during the isolation period. Besides medicine, 32 respondents (60,4%) taking vitamin c supplements,61 respondents (30,2%) taking vitamin d supplements, 1 respondents (1,9%) taking vitamin e supplements, and 2 respondents (3,8%) taking zink supplements.